Degraded lands and their management for rehabilitation and improving crop productivity - SHARMA, M. P.; SAMANTA, A.; SHARMA, K R. (Journal of Soil and Water Conservation, 2018)
Soil degradation causes decline in its productivity, deterioration in vegetative cover, qualitative, and quantitative decline of soil and water resources and pollution of air is widespread in India. In recent decades, the problem is greatly aggravated because of country’s increasing population, requiring marginal areas to be brought under the cultivation to meet the growing food demand. Poverty and natural resources degradation forced individuals to search for more land for food, fodder and fibre production. The main causes of degradation due to direct/indirect human intervention are deforestation and removal of natural vegetation, overgrazing, and converting forest lands to arable land, cultivating steep slopes and degrading marginal lands, other agriculture related activities and over exploitation of the vegetation for domestic purposes. Similarly, the removal or in-situ burning of crop residues, minimum addition of organic manures, and intensive cultivation are the major causes of the depletion of soil organic carbon (SOC). Potential threats to the conservation of soil resources are soil erosion both by water and air, salinization/ alkalinity, acidity, organic carbon (OC) losses, nutrient imbalance, pollution/contamination by toxic substances, and soil sealing and capping. To arrest the process of degradation, urgent measures viz., indigenous soil and land conservation practices, conservation farming, watershed management including land and water management technology, water harvesting, Integrated plant nutrient supply, (IPNS), physical, mechanical, and biological approach, soil amendments, restoration of SOC, aforestation and agro-forestry, farming system approach, and organic farming, etc. are required for rehabilitating productivity of degraded soils so that more food could be produced to provide livelihood and environmental security to the ever increasing Indian population.